IL-33 Deficiency Attenuates Lung Inflammation by Inducing Th17 Response and Impacting the Th17/Treg Balance in LPS-Induced ARDS Mice via Dendritic Cells - Li Cheng; Yang Jiao; Wei Jiang; Xin Zhang; Liping Zhang; Gongwei Jia (Journal of Immunology Research)
Objectives. The characteristic pathophysiological feature of acute respiratory distress syndrome (ARDS) is a dysregulated inflammatory response. T helper 17 (Th17) cells in the lung are inflammatory cells that contribute to pulmonary inflammatory cascades. In addition, Th17/regulatory T cells (Treg cells) also play an important role in the inflammatory process. Dendritic cells (DCs) can regulate the differentiation of CD4+ T cells, including Th17 and Treg cells. Recent evidence revealed that interleukin-33 (IL-33) signaling could activate and mature DCs. Therefore, the aim of this study was to investigate the effects of IL-33 on inflammation and immunoregulation by inducing the Th17 response and influencing the Th17/Treg balance in LPS-induced ARDS. Methods. IL-33 gene knockout mice and the administration of recombinant mouse IL-33 (rmIL-33) were used to investigate the role of IL-33 and the underlying mechanisms in an LPS-induced ARDS model. Hematoxylin and eosin (H&E) staining, wet/dry (W/D) weight ratios, cell counts, and the levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-17 (IL-17), and interleukin-10 (IL-10) in bronchoalveolar lavage fluid (BALF) were investigated. The levels of IL-33, orphan nuclear receptor gamma t (RORγt), and forkhead transcription factor protein 3 (FOXP3) protein in lung tissue were evaluated by Western blotting. The mRNA expression levels of IL-33 and RORγt were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Th17 and Treg cell frequencies were determined by flow cytometry. The levels of IL-6 in the supernatant in a dendritic cell culture system were examined by ELISA. Results. Increased expression of IL-33 was observed in mice with LPS-induced ARDS. IL-33 deficiency significantly inhibited inflammation and attenuated LPS-induced ARDS, whereas pretreatment with rmIL-33 aggravated pulmonary inflammatory response. Furthermore, depletion of IL-33 inhibited Th17 cells, significantly decreased RORγt mRNA and protein expression and IL-17 levels in BALF, and led to less differentiation of T cells into Th17 cells than Treg cells. Moreover, IL-33-/- DCs secreted less IL-6 and IL-23 than normal control DCs. Conclusion. IL-33 deficiency alleviated lung injury in the LPS-induced ARDS model, which was closely related to suppressing Th17 responses and regulating the Th17/Treg balance. The expansion of Th17 cells and imbalance in Th17/Treg cells may be associated with IL-6 and IL-23 secreted from IL-33-activated DCs.